2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091431
|View full text |Cite
|
Sign up to set email alerts
|

Classification of hand posture from electrocorticographic signals recorded during varying force conditions

Abstract: In the presented work, standard and high-density electrocorticographic (ECoG) electrodes were used to record cortical field potentials in three human subjects during a hand posture task requiring the application of specific levels of force during grasping. We show two-class classification accuracies of up to 80% are obtained when classifying between two-finger pinch and whole-hand grasp hand postures despite differences in applied force levels across trials. Furthermore, we show that a four-class classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…This potentially mitigates some inflammatory burden on the brain. ECoG signals have been found to encode information about arm and hand movements (Leuthardt et al, 2004; Schalk et al, 2007; Crone et al, 1998; Miller et al, 2007; Pistohl et al, 2008; Wang et al, 2009; Kubánek et al, 2009; Ball et al, 2009; Miller et al, 2009; Chao et al, 2010; Acharya et al, 2010; Degenhart et al, 2011a; Shimoda et al, 2012; Chestek et al, 2013; Nakanishi et al, 2013), as well as auditory (Edwards et al, 2005; Trautner et al, 2006), visual (Lachaux et al, 2005), language (Crone et al, 2001; Mainy et al, 2007; Kellis et al, 2010; Wang et al; 2011, Pei et al, 2011), and attentional processes (Tallon-Baudry et al, 2005; Jung et al, 2008; Ray et al, 2008). Encouraged by these findings, researchers have begun to investigate ECoG as a potential source of control signals for BMI devices.…”
Section: Introductionmentioning
confidence: 99%
“…This potentially mitigates some inflammatory burden on the brain. ECoG signals have been found to encode information about arm and hand movements (Leuthardt et al, 2004; Schalk et al, 2007; Crone et al, 1998; Miller et al, 2007; Pistohl et al, 2008; Wang et al, 2009; Kubánek et al, 2009; Ball et al, 2009; Miller et al, 2009; Chao et al, 2010; Acharya et al, 2010; Degenhart et al, 2011a; Shimoda et al, 2012; Chestek et al, 2013; Nakanishi et al, 2013), as well as auditory (Edwards et al, 2005; Trautner et al, 2006), visual (Lachaux et al, 2005), language (Crone et al, 2001; Mainy et al, 2007; Kellis et al, 2010; Wang et al; 2011, Pei et al, 2011), and attentional processes (Tallon-Baudry et al, 2005; Jung et al, 2008; Ray et al, 2008). Encouraged by these findings, researchers have begun to investigate ECoG as a potential source of control signals for BMI devices.…”
Section: Introductionmentioning
confidence: 99%
“…In ECoG studies, initial human investigations, including real‐time BCI and neuroscience experiments, were conducted in patients being observed in an epilepsy monitoring unit (EMU) . ECoG during epilepsy monitoring has been used by a number of research groups to enable the development of software and training techniques with human participants .…”
Section: Summary Of Translational Approachmentioning
confidence: 99%
“…This work guided development of subsequent human study protocols and IDE applications. Finally, the EMU study generated critical pilot data and initial funding from multiple agencies that made it possible for us to form and grow our clinical BCI research team with a demonstrated track record. The EMU research conducted in patients undergoing clinical brain mapping in itself has important scientific, engineering, and clinical value as exemplified by the ever‐increasing number of research groups and publications based on this study setting …”
Section: Foundational Studiesmentioning
confidence: 99%
See 2 more Smart Citations